The interaction of fire and mankind: Introduction(†) - Scott, Andrew C. (Philos Trans R Soc Lond B Biol Sci, 2016)
Fire has been an important part of the Earth system for over 350 Myr. Humans evolved in this fiery world and are the only animals to have used and controlled fire. The interaction of mankind with fire is a complex one, with both positive and negative aspects. Humans have long used fire for heating, cooking, landscape management and agriculture, as well as for pyrotechnologies and in industrial processes over more recent centuries. Many landscapes need fire but population expansion into wildland areas creates a tension between different interest groups. Extinguishing wildfires may not always be the correct solution. A combination of factors, including the problem of invasive plants, landscape change, climate change, population growth, human health, economic, social and cultural attitudes that may be transnational make a re-evaluation of fire and mankind necessary. The Royal Society meeting on Fire and mankind was held to address these issues and the results of these deliberations are published in this volume. This article is part of the themed issue ‘The interaction of fire and mankind’.